Analisis Dampak Perubahan Masyarakat Dalam Era Revolusi Digital Terhadap Pendapatan Sayur Online Selama Pandemi Covid-19 (Studi Kasus Pada Prabufresh Prabumulih) - Meirani Meirani Betriana; Linggariama Linggariama (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
Analysis of the Impact of Changes in Society in the Digital Revolution Era on Online Vegetable Sales Business Income (Case Study of Prabufresh Prabumulih). This study aims to determine the impact of changes in society in the era of the digital revolution on Prabu Fresh's business income during the COVID-19 pandemic. The type of research used in this study is a comparative study, namely by comparing Prabufresh's income from before and during the covid-19 pandemic. The type of data in this study is quantitative data with a sample in the form of Prabufresh's income data before and during covid-19, where the sampling technique used is purposive sampling, namely a sampling method with a specific purpose, in this case the sampling technique is based on the research objectives, namely data before and after during the covid-19 pandemic. The research method used is a quantitative descriptive analysis method, namely a research method that aims to create a description, picture or painting expressed in the form of numbers. The quantitative descriptive analysis method makes it easier for researchers to know and describe how Prabufresh's income was before and during the covid-19 pandemic. The results obtained from this study are that there is an increase in the number of customers from before and during the covid-19 pandemic which, if presented, has increased by approximately 33%. Due to the increase in the number of Prabufresh customers as a result of changes in society in the era of the digital revolution, this also has an impact on Prabufresh's income which has also increased from before and during the covid-19 pandemic. If you look at the amount of income before covid-19, which was Rp. 105,678,900 and during covid-19 it was Rp. 214,470,350, there was an increase in income of Rp. 108,791,450, - which if percentage the increase was more than 100%, namely 102.95%. The increase in the amount of Prabufresh's income is due to changes in people's patterns or habits from shopping traditionally to shopping online due to the covid-19 pandemic, where the increasing number of customers will certainly increase the business income obtained by Prabufresh Keywords: Society Change, Digital Revolution, Income